Circulating T‐helper 17 cells and associated cytokines in psoriasis. (2nd August 2016) - Chhabra, S.; Narang, T.; Joshi, N.; Goel, S.; Sawatkar, G.; Saikia, B.; Dogra, S.; Bansal, F.; Minz, R.
Summary: Background: Recently, a new population of IL‐17‐producing CD4 T helper (Th) cells, named Th17, was identified and shown to be involved in various inflammatory and autoimmune diseases, including psoriasis. Aim: To determine the frequency of Th17 cells and related cytokines in peripheral blood of patients with psoriasis, and to analyse their association with disease severity. Methods: This was a prospective study comprising 34 patients with psoriasis and 24 healthy controls. Clinicoepidemiological details of patients were recorded, and severity of psoriasis was assessed by means of the Psoriasis Area and Severity Index. Circulating Th1 and Th17 cells in untreated patients with psoriasis and healthy controls were quantified by flow cytometry. In sera collected from patients with psoriasis and healthy controls, concentrations of IL‐17A and IL‐23 were examined by ELISA. Results: Increased frequencies of CD4+ IL‐17A+ T cells were seen in peripheral blood of patients with psoriasis vulgaris ( P < 0.001). Although serum IL‐17A and IL‐23 concentrations were higher in patients with psoriasis than in controls, the results did not reach statistical significance. We could not find any correlation between the studied T cells or related cytokines and the disease severity. Conclusion: Increased serum levels of circulating Th17 cells and related cytokines may contribute to the cutaneous pathology of psoriasis, as well as the inflammatory process that is a hallmark of psoriasis.